2016
DOI: 10.15237/gida.gd15060
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF DIFFERENT DEBITTERING METHODS ON TOTAL PHENOLIC MATTER and FLAVONOID CONTENT INTRADITIONAL BITTER ORANGE PEEL JAM

Abstract: Bu çal›flmada, Akdeniz Bölgesi'nde yayg›n olarak üretilen geleneksel turunç kabu¤u reçeli üretiminde hammaddedeki ac›l›k bileflenlerinin uzaklaflt›r›lmas›nda farkl› ac›l›k giderme yöntemlerinin etkinli¤inin belirlenmesi amaçlanm›flt›r. Ac›l›k giderme yöntemlerinin etkinli¤i toplam fenolik, toplam flavonoid ve ac› flavonoidlerin miktar›ndaki de¤iflimle belirlenmifltir. Bu amaçla 19 farkl› ac›l›k giderme yöntemi uygulanm›fl olup bunlardan üçü di¤erlerine göre ifllem süresi aç›s›ndan daha avantajl› bulunmufltur. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Results of the consumer study showed that the instrumental results which were related to the bitterness perception question (gLMS response) were the ones of the TPC, although flavonoid content had been previously related to bitter compounds determination (Hasegawa et al ., 1996). Alkali treatment and subsequence washing, and soaking, has been reported as an efficient method to debitter OPs (Yıldız Turgut et al ., 2016). Also, similar treatments have been used for debittering olives, showing a loss of bioactive compounds such as phenolic compounds (TPC) when compared to fresh olives (Alexandraki et al ., 2014; Berlanga‐Del Pozo et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of the consumer study showed that the instrumental results which were related to the bitterness perception question (gLMS response) were the ones of the TPC, although flavonoid content had been previously related to bitter compounds determination (Hasegawa et al ., 1996). Alkali treatment and subsequence washing, and soaking, has been reported as an efficient method to debitter OPs (Yıldız Turgut et al ., 2016). Also, similar treatments have been used for debittering olives, showing a loss of bioactive compounds such as phenolic compounds (TPC) when compared to fresh olives (Alexandraki et al ., 2014; Berlanga‐Del Pozo et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, samples were rinsed and left in tap water for 48 h to remove the remains of Na 2 CO 3 as recommended by Yıldız Turgut et al . (2016). Salt blanching using 2% NaCl (SALT sample).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations